Analysis of the Dimension of the Quality of Service with Online Registration System Again to Increase Patient Satisfaction in Outpatient Room of Jombang General Hospital - Masrulloh Masrulloh; Sentot Imam Suprapto; Yuly Peristiowati (Journal for Quality in Public Health, 2020)
Granting of services on patients the best should give fast service, so that patients are not left waiting a long time to get good, turn at the time of registration or get a room and also at the time of payment. Customers come to your place of service by the time that random, irregular and cannot immediately be served so they have to wait in a long time. In studying the theory of queues, service providers are able to cultivate in order to serve its customers well without having to wait for a long time. The purpose of this research was to analyze the effect of the dimensions of the quality of service with online registration system with increased Patient satisfaction In Outpatient Room of Jombang General Hospital. Design of this research are analytic observational design with a quantitative approach. Variable Dimension, namely the quality of service research online registration (Accuracy, readiness, Speed response) as the independent variable. Patient satisfaction as the dependent variable. The population of this research the whole of patient at Outpatient Room of Jombang General Hospital. as much as 625 patients. Samples taken with the cluster random sampling technique as much as 125 respondents. Data is collected with instruments ceklist and processed in coding, editing, tabulating and scoring as well as tested with linear regression test. Linear regression results indicate that partially and simultaneously the value of p values there are shows < 0,05 so that thereis influence the dimensions of quality of service with online registration system with increased Patient satisfaction In Outpatient Room of Jombang General Hospital. The existence of the speed of service, timeliness of service and readiness the implementation of online registration will affect patient satisfaction. Because the patient will feel comfortable with fast service and not too long to wait, and also with the proper services are provided in accordance with the complaint and adequate facilities